2012
DOI: 10.1371/journal.pone.0050993
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Compressed Collagen as a Novel Carrier for Expanded Human Corneal Endothelial Cells for Transplantation

Abstract: Current treatments for reversible blindness caused by corneal endothelial cell failure involve replacing the failed endothelium with donor tissue using a one donor-one recipient strategy. Due to the increasing pressure of a worldwide donor cornea shortage there has been considerable interest in developing alternative strategies to treat endothelial disorders using expanded cell replacement therapy. Protocols have been developed which allow successful expansion of endothelial cells in vitro but this approach re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 24 publications
1
88
0
2
Order By: Relevance
“…These results suggested that propagated hCECs were amenable to the dual media approach presented in this study and could be plated at a higher density to achieve a denser monolayer of CECs with compact cellular pattern. Indeed, when seeded at a higher density onto a compressed collagen-based hydrogel (a potential transplantable corneal graft substitute), a cell density of approximately 1,941 cells per mm 2 was achieved (33).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that propagated hCECs were amenable to the dual media approach presented in this study and could be plated at a higher density to achieve a denser monolayer of CECs with compact cellular pattern. Indeed, when seeded at a higher density onto a compressed collagen-based hydrogel (a potential transplantable corneal graft substitute), a cell density of approximately 1,941 cells per mm 2 was achieved (33).…”
Section: Discussionmentioning
confidence: 99%
“…Compressed Type 1 collagen using the RAFT technology, as described above, has been investigated as a potential substrate for the expansion and delivery of corneal endothelial cells. [45] It was demonstrated that the mechanical properties of the samples were sufficient to be clinically manipulated into an eye using the standard transplant instruments. Furthermore, primary human corneal endothelial cells were demonstrated to attach and grow as a monolayer on the RAFT substrates and showed evidence of tight junctions and functional behavior after only 4 d of culture while maintaining their endothelial phenotypic morphology in longer term cultures.…”
Section: Endotheliummentioning
confidence: 99%
“…60,[69][70][71][72][73][74] Decellularized aminiotic membrane was clinically evaluated in combination with human corneal endothelial cells in a lamellar keratoplasty model, where the removal of the endothelium and part of the Descemet's membrane was performed and able to function as a corneal endothelium equivalent. 73 …”
Section: Corneal Endotheliummentioning
confidence: 99%